My fair zombie [videorecording (DVD)] - Kelly, Brett; Payer, Trevor; Evenchick, Lawrence; Gabriel, Sacha; Caiger, Barry ([Publisher not identified], 2014)
My Fair Zombie : In an alternate Edwardian England infested by zombies, a professor of phonetics attempts to teach a zombie woman to be a proper English lady, with hilarious and gore-soaked results! Based on the play by George Bernard Shaw. Spyfall : When it comes to action, he's your last resort! When a fellow agent fails in his mission to recover the MacGuffin, Canada's greatest spy is called in to finish the job.